Chemical Constituents and Antibacterial Activity of Essential Oil of Peucedanum ruthenicum M. Bieb. Fruits: Peucedanum ruthenicum essential oils - Alavi, Seyed Hamid Reza; Yassa, Narguess; Fazeli, Mohamad Reza (Iranian Journal of Pharmaceutical Sciences, 2005)
The essential oil of Peucedanum ruthenicum fruits, obtained by hydrodistillation, was analyzed by gas chromatography and gas chromatography-mass spectrometry. Among the 31 identified constituents accounting for 83.9% of the total oil, the major components were 1,8-cineole (11.15%), camphor (5.86%), Z-carveol (6.88%), lcarvone (5.61%), 8,9-dehydroisolongifolene (11.35%), caryophyllene oxide (13.65%), and caryophylla-4(12),8(13)-dien-5-β-ol (5.19%). Antimicrobial activity of the essential oil was investigated against various gram-positive and gram-negative bacteria. The essential oil of P. ruthenicum showed activity against gram-positive bacteria but had no effect on the tested gram negative bacteria.